A review of the child and adolescent mental healthcare services at Rahima Moosa Hospital - Raman, Natali (My University, 2011)
Introduction: National and international child and adolescent mental healthcare policy and action advocate that the health and well-being of children in South Africa should be increasingly given greater attention. Child and adolescent services have recently been established at Rahima Moosa Hospital. The purpose of this study was to describe the scope, capacity and diagnostic profile of existing child and adolescent mental health and psychiatric services at Rahima Moosa Hospital within the context of the available infrastructure and service rendering and to describe the demographic and clinical profile of the users. Method: A descriptive, retrospective clinical audit study of the data from users‟ clinical files was performed. The study population comprised all users treated at the Rahima Moosa Hospital over a one-year period from January to December 2007. Descriptive statistical analyses of demographic and socio-economic variables were made and these variables were compared with the presenting clinical problems. P-values of less than 0.05 were regarded as significant. Odds ratios were also calculated for variables that showed a statistically significant association. Results: During this period a total of 303 users attended this clinic. Their age, gender, race and catchment area was reviewed. Socio-economic variables that were described included caregiver of user, placement, parents‟ well being and marital status, educational level of caregiver and household income. Most common disorders were Attention Deficit Hyperactivity Disorder (ADHD), Mood, Anxiety, Elimination, Attachment, Disruptive behaviour disorders and V-code diagnoses. Although not regarded as psychiatric diagnoses, V-codes are problems that are the focus of clinical attention. These include 5 sexual abuse, academic problems and parent-child relationship difficulties. Statistical comparisons between demographic data and disorders revealed that being male increased the likelihood of presenting with AHDH and disruptive behaviour disorders; being female increased the likelihood of being sexually abused. Race showed a significant association with parent-child relationship difficulties. Regarding socio-economic variables, the identity of the caregiver of the child influenced the risk of disruptive behaviour disorders, sexual abuse, neglect and academic problems. Placement was a risk factor for disruptive behaviour disorders, sexual abuse, neglect and academic problems. Whether the mother of a user was alive or deceased was related to ADHD and disruptive behaviour and whether the father of a user was alive or deceased was related to sexual abuse and academic problems. The education level of the caregiver showed a significant association with sexual abuse, neglect and academic problems; the marital status of the parents showed a significant association with bereavement. Household income was associated with sexual abuse, neglect and academic problems. Type of housing showed an association with the risk of sexual abuse. Discussion: This study clearly demonstrates the huge impact that socio-economic circumstances have on the prevalence of childhood disorders; hence the urgent need for government and social welfare departments to improve on the socio-economic status of communities. Job creation and employment will lead to better outcomes and help lower the incidences of childhood illnesses. The focus should be on preventative measures, that is, improving the social well-being of both children and their parents, which will result in lower prevalence of disease. Moreover, interventions in schools and children‟s homes should be 6 implemented. The provision of psycho-education for the group in the catchment with regard to identification of mental health problems can contribute to the early detection of mental illness and early intervention leading to a reduction in disease. Conclusion: In spite of government‟s initiative to prioritise child and adolescent mental health services in South Africa, further endeavours are required to improve psychiatric services among this section of the population, including more clinics and child psychiatry training posts and extended social work services. Socio-economic factors influence the prevalence of childhood disorders. Hence, modifying the environment to which these children are exposed is an integral part of the holistic treatment approach
MMed, Psychiatry, Faculty of Health Sciences, University of the Witwatersrand
Keywords: child mental health services; adolescent mental health services